Multicenter validation of the American Association for the Surgery of Trauma grading scale for acute cholecystitis. Issue 1 (January 2021) - Schuster, Kevin M.; O'Connor, Rick; Cripps, Michael; Kuhlenschmidt, Kali; Taveras, Luis; Kaafarani, Haytham M.; El Hechi, Majed; Puri, Ruchir; Mull, Jennifer; Schroeppel, Thomas J.; Rodriquez, Jennifer; Cullinane, Daniel C.; et al.
Abstract : BACKGROUND: The American Association for the Surgery of Trauma (AAST) patient assessment committee has created grading systems for emergency general surgery diseases to assist with clinical decision making and risk adjustment during research. Single-institution studies have validated the cholecystitis grading system as associated with patient outcomes. Our aim was to validate the grading system in a multi-institutional fashion and compare it with the Parkland grade and Tokyo Guidelines for acute cholecystitis. METHODS: Patients presenting with acute cholecystitis to 1 of 8 institutions were enrolled. Discrete data to assign the AAST grade were collected. The Parkland grade was collected prospectively from the operative surgeon from four institutions. Parkland grade, Tokyo Guidelines, AAST grade, and the AAST preoperative grade (clinical and imaging subscales) were compared using linear and logistic regression to the need for surgical "bailout" (subtotal or fenestrated cholecystectomy, or cholecystostomy), conversion to open, surgical complications (bile leak, surgical site infection, bile duct injury), all complications, and operative time. RESULTS: Of 861 patients, 781 underwent cholecystectomy. Mean (SD) age was 51.1 (18.6), and 62.7% were female. There were six deaths. Median AAST grade was 2 (interquartile range [IQR], 1–2), and median Parkland grade was 3 (interquartile range [IQR], 2–4). Median AAST clinical and imaging grades were 2 (IQR, 2–2) and 1 (IQR, 0–1), respectively. Higher grades were associated with longer operative times, and worse outcomes although few were significant. The Parkland grade outperformed the AAST grade based on area under the receiver operating characteristic curve. CONCLUSION: The AAST cholecystitis grading schema has modest discriminatory power similar to the Tokyo Guidelines, but generally lower than the Parkland grade, and should be modified before widespread use. LEVEL OF EVIDENCE: Diagnostic study, level IV. Abstract : Supplemental digital content is available in the text.